2007
DOI: 10.1152/jn.00413.2006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Processing of Saccade Targets in Parietal Cortex Area LIP During Visual Search

Abstract: Thomas NW, Paré M. Temporal processing of saccade targets in parietal cortex area LIP during visual search. J Neurophysiol 97: [942][943][944][945][946][947] 2007. First published November 1, 2006; doi:10.1152/jn.00413.2006. We studied whether the lateral intraparietal (LIP) area-a subdivision of parietal cortex anatomically interposed between visual cortical areas and saccade executive centers-contains neurons with activity patterns sufficient to contribute to the active process of selecting saccade targets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
177
4
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(207 citation statements)
references
References 22 publications
24
177
4
2
Order By: Relevance
“…Our single-and multiple-distractor tasks were effectively pop-out tasks (targets and distractors differed in color) and therefore similar to the pop-out task used in Buschman and Miller (2007). As a population, LIP neurons detected the location of the target as early as 52 ms after stimulus onset, which is similar to the 50 ms selectivity latency of the fastest neurons reported by Buschman and Miller (2007) but much faster compared with other LIP studies (Thomas and Paré, 2007;Ipata et al, 2009), and considerably faster than the oddballdetection latencies reported for FEF (130 -140 ms) (Schall et al, 2007). Importantly, these short selectivity latencies cannot be explained by the mere difference in visual stimulation in the RF (target and distractor vs distractor in RF), as we obtained equally short latencies in the single-distractor saccade task (target vs distractor in RF).…”
Section: Discussionsupporting
confidence: 68%
“…Our single-and multiple-distractor tasks were effectively pop-out tasks (targets and distractors differed in color) and therefore similar to the pop-out task used in Buschman and Miller (2007). As a population, LIP neurons detected the location of the target as early as 52 ms after stimulus onset, which is similar to the 50 ms selectivity latency of the fastest neurons reported by Buschman and Miller (2007) but much faster compared with other LIP studies (Thomas and Paré, 2007;Ipata et al, 2009), and considerably faster than the oddballdetection latencies reported for FEF (130 -140 ms) (Schall et al, 2007). Importantly, these short selectivity latencies cannot be explained by the mere difference in visual stimulation in the RF (target and distractor vs distractor in RF), as we obtained equally short latencies in the single-distractor saccade task (target vs distractor in RF).…”
Section: Discussionsupporting
confidence: 68%
“…For example, activity related to eye-movement target selection has been identified in the superior colliculus (SC) (7,(11)(12)(13)(14)(15)(16)(17), frontal eye field (18)(19)(20), lateral intraparietal area (10,(21)(22)(23), and supplementary eye fields (24), all areas in which signals related to eye movement execution are seen and in which electrical microstimulation and/or temporary inactivation affects the execution of eye movements (25)(26)(27)(28)(29)(30)(31). For reaching movements, target selection activity has been observed in the dorsal premotor area (32)(33)(34), a region from which reaches can be electrically elicited (35), as well as in the parietal reach region (36,37), which exhibits reach-related planning and execution signals (38,39).…”
mentioning
confidence: 99%
“…Then, we also found changes in the inferior occipital gyrus that could be linked to the PPC. On visual search tasks designed to investigate the priority map function, it has been observed that occipital gyrus neurons do not respond to task demands as the PPC does; the PPC responds more to targets than the occipital gyrus (Ipata et al, 2006;Buschman and Miller, 2007;Thomas and Paré, 2007;Mirpour et al, 2009). The decreased activation in occipital gyrus areas could be explained by repetition suppression mechanisms .…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this hypothesis, researchers have been observing that maps in early visual areas do not respond to task demands like the PPC does. For example, during visual search tasks, enhanced PPC response was observed more for targets than for distractors (Ipata et al, 2006;Buschman and Miller, 2007;Thomas and Paré, 2007;Mirpour, Arcizet, Ong and Bisley, 2009). It seems that during visual search tasks, the focus of attention is guided through the visual scene using the priority map, where the targets are highlighted and the distractors are suppressed .…”
Section: Priority Maps and Posterior Parietal Cortexmentioning
confidence: 99%
See 1 more Smart Citation